Phenomenology Study of Corporate Social Responsibility: Perspective of PT. Petrokimia Gresik Management - Eko Widodo; Eko Ganis Sukoharsono; Kliwon Hidayat; M. Sasmito Djati (Sekolah Pascasarjana Universitas Brawijaya, 2017)
This research approach is qualitative research based on phenomenology. The essence of phenomenological study is to describe the views, knowledge, as well as the interpretation of a concept or phenomenon of subjects with a particular phenomenon, therefore, this study aims to understand the meaning of the concept of corporate social responsibility from the perspective of PT. Petrokimia Gresik management. The results showed that PT. Petrokimia Gresik management interprets the concept of corporate social responsibility (1). as accountability to the government; (2). as accountability to shareholders; (3). as accountability to the public; (4). as accountability to the environment; (5). as accountability to employees; and (6). as accountability to customers.